William Shakespeare complete works - Shakespeare, William 1564-1616 (MacMillan Publishers Ltd, 2007)
Developed in partnership with The Royal Shakespeare Company, this edition of the Complete Works of William Shakespeare combines exemplary textual scholarship with elegant writing and design. Sir Jonathan Bate and Professor Eric Rasmussen, two of today's most accomplished Shakespearean scholars, lead the expert editorial team. Bate's excellent general introduction and essays on each play draw on a unique wealth of experience and resources and will help the reader to understand Shakespeare's plays as they were originally intended - as living theatre to be enjoyed and performed. The text is based on the iconic 1623 First Folio: the first and original Complete Works lovingly assembled by Shakespeare's fellow actors and the version of Shakespeare's text preferred by many actors and directors today. The result is a fresh and definitive Complete Works for the twenty-first century that will inspire students, teachers and lovers of Shakespeare everywhere